Helen Keller International (HKI) OFSP Update – Africa Region - International Potato Center (2017)
Across six countries in Africa, HKI is working in partnership to support orange-fleshed sweetpotato (OFSP) development, production, and consumption as part of an integrated nutrition-sensitive agriculture approach. We have achieved numerous successes and continue to search for new ways to innovatively support the growth of OFSP.